Markov Switching Oil Price Uncertainty. (4th February 2019) - Serletis, Apostolos; Xu, Libo
Abstract: We investigate whether the United States economy responds negatively to oil price uncertainty and whether oil price shocks exert asymmetric effects on economic activity. In doing so, we relax the assumption in the existing literature that the data are governed by a single process, modifying the Elder and Serletis (2010) bivariate structural GARCH‐in‐Mean VAR to accommodate Markov regime switching in order to account for changing oil price dynamics over the sample period. We find evidence of asymmetries, against those macroeconomic theories that predict symmetries in the relationship between real aggregate economic activity and the real price of oil.